(untitled) - Hejhalova, Bozena (Doprava a spoje, 2010)
Standards of quality for transport services determining a uniform level of services in the region. Based on the requirements on the quality of passenger transport services, customers of transport performances, acceptance of the requirements, give the guarantee to passengers for a range of services on the "standard" level. The result may be to increase the quality and attractiveness of public passenger transport and favorable developments in the share of public passenger transport in total transport performance.